Design, Implementation, and Evaluation of a Mobile Application for Patient Empowerment and Management of Long-Term Follow-Up after Childhood Cancer. - Kock, Ann-Kristin; Kaya, Rafiye; Müller, Christian; Björn Andersen; Langer, Thorsten; Ingenerf, Josef (Klinische Padiatrie, 2015)
In Germany, about 1 800 new cases of childhood cancer are diagnosed every year. The chances of survival have increased significantly over the last 40 years due to the continuous improvement of treatment strategies. The number of childhood cancer survivors in Germany thus ranges around 30 000 nowadays. But their treatment with surgery, chemotherapy, and radiation has certain side-effects. In addition to the acute effects during the treatment phase, the disease- and treatment-related late effects can occur even decades after the end of therapy. These late effects draw attention as the survival rate constantly increases. Two-thirds of the former patients retain long-term consequences, nearly a fifth with a resulting diminished quality of life. Early detection of these late effects can help to reduce or even to prevent serious health damage. Therefore, the study group LESS supplies long-term follow-up recommendations for former patients. The project described in this paper was to design and implement a mobile application to increase the compliance for this aftercare program. This application provides information about the patient's individual aftercare plan and supports appointment management as well as a reminding functionality. A prototype for former osteosarcoma patients was tested and evaluated in two university hospitals. First results show the application's very high potential for patient empowerment.